Clinical outcomes of single-incision sling procedure (MiniArc) - Tsia-Shu Lo; Eileen Feliz M. Cortes; Pei-Ying Wu; Yiap Loong Tan; Leng Boi Pue; Ahlam Al-Kharabsheh (Wolters Kluwer Medknow Publications, 2015)
Objective: To evaluate the clinical outcome among women who had undergone Miniarc™ in the treatment of stress urinary incontinence (SUI). Study design: In this retrospective study from March 2010 to December 2011 patients with clinically confirmed SUI and urodynamic stress incontinence (USI) underwent Single Incision Sling Procedure (SIS). Objective cure of SUI was defined as no urinary leakage on provocative filling cystometry and 1-hour pad test of <2 g. Subjective cure of SUI was the negative response to UDI-6. Assessment was done at baseline and after 1 year follow-up. Results: Postoperative data was available for 85 women. Five women were not able to participate in the follow-up schedule and post-op questionnaire. The objective data for post-operative follow-up was available from 80 women. The average period of follow-up was 1.4 years (range 1.0 to 2.1). A total of 14 women had immediate post-operative urine retention at the first 24 hours and 6 cases were due to over-tensioning of the sling after ultrasound assessment. No case of bladder or bowel injury was recorded and no other major complications noted. Pre and post clinical findings revealed a significant improvement after 1 year follow-up based on the response to UDI-6, IIQ-7 (<0.001) and PISQ-1 (0.12). Urodynamic parameters revealed an increase in MUCP however the other urodynamic parameters had no statistical difference (p > 0.05). Conclusions: In conclusion, Miniarc™ was noted to have improvement in both subjective and objective clinical outcomes. Urethral indentation was noted and resolved by tape release on immediate post-operative voiding dysfunction.